Antibacterial Activity of Compounds Synthesized From 4-Chloro-3-nitro-2H-[1]-benzopyran-2-one - Vaso, Kozeta; Behrami, Aziz; Krasniqi, Islam (Asian Journal of Chemistry, 2010)
In present paper, the synthesis and the antibacterial activity of two compounds from 4-chloro-3- nitro-2H-[1]-bezopyran-2-one are reported. Compounds 4-(b-naphthyl amino)-3-nitro-2H-[1]- benzopyran-2-one (b1) and 4-(4-amino-2,6-dyhydroxypyrimidine)-3-nitro-2H-[1]-benzopyran- 2-one (b2) have been characterized using melting points, IR spectra, 1H and 13C NMR spectra. The antibacterial activity of synthesized compounds and streptomycin at concentrations of 1, 3 and 5 mg/mL have been evaluated against three strains of bacterial culture i.e., Staphylococcus aureus, Escherichia coli and Klebsiella. The compunds show bacteriostatic and bactericidal activity.